2007
DOI: 10.1590/s0004-282x2007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Concentric needle single fiber electromyography: normative jitter values on voluntary activated Extensor Digitorum Communis

Abstract: Single fiber electromyography (SFEMG) is the most sensitive clinical neurophysiological test for neuromuscular junction disorders, particularly myasthenia gravis. Normal values for jitter obtained with SFEMG electrode have been published, but there are few publications for concentric needle electrode (CNE). The aim of this study was to discuss the possibilities to analyse the jitter in CNE recordings and to get normal values of jitter for voluntary activated Extensor Digitorum Communis using disposable CNE. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 11 publications
1
32
0
3
Order By: Relevance
“…We have done it in some previous reports for ED and OOc muscles, both for voluntary and stimulated techniques and FR stimulated 10,[20][21][22][23][24] . A few studies that have compared jitter values from SFEMG and from CNE in healthy controls and patients with MG reported a good correlation between results [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have done it in some previous reports for ED and OOc muscles, both for voluntary and stimulated techniques and FR stimulated 10,[20][21][22][23][24] . A few studies that have compared jitter values from SFEMG and from CNE in healthy controls and patients with MG reported a good correlation between results [6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have presented normative data and diagnostic value of the test in MG [7][8][9][10][11][12][13] . Farrugia et al 14 found no differences in mean jitter values for extensor digitorum (ED) and OOc muscles in 24 MG patients using both SFE and CNE.…”
mentioning
confidence: 99%
“…Recentemente, com a necessidade crescente de utilização de material descartável em procedimentos médicos, incluindo os eletrodos de agulha utilizados em eletroneuromiografia (ENMG), iniciou-se uma série de estudos usando eletrodos de agulha convencionais descartáveis, por exemplo, a agulha monopolar (Wiechers, 1985;Buchman, Garratt, 1992;Tutkavul, Baslo, 2010) e a agulha concêntrica (AC) (Ertaş et al, 2000;Benatar et al, 2006;Sarrigiannis et al, 2006;Kouyoumdjian, Stålberg, 2007;2008a;2008b;2013a). Em comparação com as agulhas monopolar e concêntrica, a AFU possui área de registro muito mais seletiva (King et al, 1997).…”
Section: Introductionunclassified
“…Adicionalmente à filtragem de sinais, são necessários cuidados técnicos na aceitação dos PAs obtidos com AC para análise do jitter (Sanders, Stålberg, 1996;Ertaş et al, 2000;Benatar et al, 2006;Sarrigiannis et al, 2006;Kouyoumdjian, Stålberg, 2007;Stålberg, Sanders, 2009 (Stålberg, Sanders, 2009;Stålberg et al, 2010). Além da velocidade de propagação nas fibras musculares individuais (Stålberg, 1966) e do jitter neuromuscular (Stålberg et al, 1971;Ekstedt et al, 1974), a EMGFU também permite o estudo da distribuição das fibras musculares nas unidades motoras individuais, denominado densidade de fibras (Gath, Stålberg, 1976).…”
Section: Introductionunclassified
See 1 more Smart Citation